Building Moderation Islam in Plural Community: Relation Between Social Media and Social Conflicts in Padang, West Sumatera-Indonesia - Reza Fahmi; Prima Aswirna (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study assumes that social media has a strong influence on social movements in society. This is highly disruptive to interactions between religious groups within the country. Additionally, the objectives of this study are to: (1) To explain the pattern of Islamic moderation growing and developing in Padang. (2) Describe the profile of Padang's social media users; (3) See the influence of moderate Islam developing through social media on the religious conflict in Padang. This study uses a quantitative approach. A total of 265 people made up the population of this study. As a result, while religious issues are a potential topic of conflict within the community, reasonable and moderate Islam has a positive impact on the people of Padang City, who are able to respect their differences. It has been shown that there is no possibility of conflict between the peoples of the United States, who love unity and prioritize peace.